My life is a weapon a modern history of suicide bombing - Reuter, Christoph (Princeton University Press, 2004)
What kind of people are suicide bombers? How do they justify their actions? In this meticulously researched and sensitively written book, journalist Christoph Reuter argues that popular views of these young men and women - as crazed fanatics or brainwashed automatons - fall short of the mark. In many cases these modern-day martyrs are well-educated young adults who turn themselves into human bombs willingly and eagerly - to exact revenge on a more powerful enemy, perceived as both unjust and oppressive. Suicide assassins are determined to make a difference, for once in their lives, no matter what the cost. As Reuter's many interviews with would-be martyrs, their trainers, friends, and relatives reveal, the bombers are motivated more by how they expect to be remembered - as heroic figures - than by religion-infused visions of a blissful life to come.